2016
DOI: 10.3390/ijms17091485
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Long Non-Coding RNAs in Human Breast Cancer

Abstract: Breast cancer represents a major health burden in Europe and North America, as recently published data report breast cancer as the second leading cause of cancer related death in women worldwide. Breast cancer is regarded as a highly heterogeneous disease in terms of clinical course and biological behavior and can be divided into several molecular subtypes, with different prognosis and treatment responses. The discovery of numerous non-coding RNAs has dramatically changed our understanding of cell biology, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 161 publications
1
62
0
Order By: Relevance
“…Accumulating evidence indicates that lncRNAs play critical roles in a spectrum of biological processes via transcriptional, post-transcriptional and epigenetic mechanisms [5]. Dysregulation of lncRNAs has been observed in various cancers, including breast cancer, colorectal cancer, lung cancer, prostate cancer as well as esophageal cancer [610]. It has been reported that dysregulated lncRNAs are associated with cancer pathogenesis and function as oncogenic or tumor suppressive regulators in cancer development [11].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that lncRNAs play critical roles in a spectrum of biological processes via transcriptional, post-transcriptional and epigenetic mechanisms [5]. Dysregulation of lncRNAs has been observed in various cancers, including breast cancer, colorectal cancer, lung cancer, prostate cancer as well as esophageal cancer [610]. It has been reported that dysregulated lncRNAs are associated with cancer pathogenesis and function as oncogenic or tumor suppressive regulators in cancer development [11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of lncRNAs have been shown to be involved in a wide range of biological functions including RNA processing, 10,11 gene transcription regulation, 1 miRNAs' host genes, 2 modulation of apoptosis and invasion, 4 marker of cell fate, 5 and chromatin modification. 6 Altered expression of lncRNAs has been documented in human gastric cancer, prompting increased interest in their potential use as biomarkers for diagnosis and prognosis, in addition to their potential roles as therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Enormous studies have proven that lncRNAs were associated with tumorgenesis, progression, metastasis, and drug resistance, functioning as oncogenes, tumor suppressor genes, or both, involving in shaping multiple biological characteristics of cancer at transcriptional, posttranscriptional, and epigenetic levels . In addition, the abnormal expression levels of different lncRNAs with oncogenic and tumor suppressor functions have been frequently found in the development of BC . Particularly, adverse rules of miRNAs‐sponging lncRNAs, involved in ceRNA networks (ceRNETs), have been shown in BC .…”
Section: Introductionmentioning
confidence: 99%